Biophysical interactions, docking studies and cytotoxic potential of a novel propofol-linolenate: a multi-technique approach. Issue 8 (23rd May 2020) - Alanazi, Amer M.; Khan, Azmat Ali; Rehman, Md. Tabish; Jabeen, Mumtaz; Algrain, Nasir; Baig, Mohammad Hassan
Abstract: In the present study, we have analyzed the biophysical interactions of alpha-linolenic acid conjugate (2, 6P-ALA) with human serum albumin (HSA) and calf thymus DNA (CT-DNA); and also determined its effect on human cancer cell lines. The results of interactions between 2, 6P-ALA and HSA intrinsic fluorescence indicated static quenching of HSA by the target conjugate with overall Stern-Volmer quenching constant ( K sv ) value of 1.8 × 10 3 M −1 . At high concentrations, 2, 6P-ALA caused conformational variations in HSA with evident increase in α-helices. Docking studies also revealed preferential binding of 2, 6P-ALA at the hydrophobic cavity of site IB with suggestive involvement of hydrophobic forces. Likewise, the conjugate was also able to quench the fluorescence intensity of CT-DNA with static type of quenching signifying the probability of interaction between them. In case of competitive interaction with ethidium bromide (EB) bound CT-DNA also; the conjugate replaced the EB depicting intercalation to be the main type of binding force. Results of cytotoxic effect of 2, 6P-ALA showed significant inhibition of cancer cells growth in a concentration-dependent manner. Conjugate was most potent on MCF-7 cells. Fluorescence microscopic image of MCF-7 cells at IC50 concentration of 24 µM revealed distinct morphological changes that were characteristic of programed cell death. Overall, these results complement with the previous findings of 2, 6P-ALA and provide added statistics about the prospect of their transport in blood plasma. Communicated by Ramaswamy H. Sarma